PAIRED ORAL TESTS: A LITERATURE REVIEW - Prasetyo, Hardi (LLT Journal: A Journal on Language and Language Teaching, 2018)
This paper reviews the studies on paired oral tests in the last ten years (2007-2017). Using the search facilities in Iowa State Universityâs library, nine articles from some journals in the field of applied linguistics were chosen based on the inclusion criteria. Those journals are Language Testing, Language Assessment Quarterly, Applied Linguistics, and Procedia â Social and Behavioral Science. Three reasons why paired oral tests are better than interview test or individual format test are then discussed. Those are promoting and improving studentsâ interactional competence, creating studentsâ co-constructed discourse, and providing insights for better scale development and rater training. Paired oral tests provide opportunities for students to interact with peers in the tests, enable them to practice and improve their interactional competence. Paired oral tests also enable students to co-construct their discourse, even though there is an issue of grading the scores individually or collaboratively. The last is, more information about studentsâ and ratersâ perception were gained that helps improve the rating scale and inform rater training. This paper is concluded with the call for more studies on paired oral tests to provide more insights into this complex process of creating co-constructed discourse and how to validly and reliably test both its process and product.DOI: doi.org/10.24071/llt.2018.Suppl2110